2011
DOI: 10.1111/j.1753-6405.2010.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

The future of public health nutrition: a critical policy analysis of Eat Well Australia

Abstract: A s the disease burden and costs of diet-related diseases in Australia are high, and are unequally distributed among the population, nutrition is considered a priority public health issue that has been gaining increasing attention over the past two decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…One article showed that there were no significant changes in school-based eating at the end of a 2-year study, although there were some positive changes in the early stage of the intervention ( 38 ) . This is consistent with other reviews, particularly those studies that actually assessed changes in dietary intake, which found no overall effect in the long term but some effect in the short term or in population subgroups ( 64 66 ) . Long-term follow-up is essential if we are to determine whether nutrition interventions offer sustained benefits ( 67 , 68 ) .…”
Section: Discussionsupporting
confidence: 92%
“…One article showed that there were no significant changes in school-based eating at the end of a 2-year study, although there were some positive changes in the early stage of the intervention ( 38 ) . This is consistent with other reviews, particularly those studies that actually assessed changes in dietary intake, which found no overall effect in the long term but some effect in the short term or in population subgroups ( 64 66 ) . Long-term follow-up is essential if we are to determine whether nutrition interventions offer sustained benefits ( 67 , 68 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Previous national nutrition activities such as the Food and Nutrition Policy (1992) and Eat Well Australia (2000‐2010) have considered addressing food and nutrition insecurity; however, these policies and programs have historically been regarded as being inadequately resourced . Accordingly, the relative abundance of responses at a state government level may in part be compensating for this lack of a national, whole‐of‐government approach to addressing FI.…”
Section: Discussionmentioning
confidence: 99%
“…25 Previous studies have demonstrated that WPR is a useful approach for interrogating how public health nutrition and childhood obesity are problematized in policy documents and media stories. [30][31][32][33] For example, analysis of Australia's now expired national public health nutrition agenda, Eat Well Australia, revealed public health nutrition was represented as an individual problem, and as a problem arising from social, political and economic circumstances. 30 Analysis of media representations of childhood obesity in Australia revealed media coverage favoured the representation of childhood obesity as a problem of individuals, in direct contrast to the social representation observed in the academic literature.…”
Section: Methodsmentioning
confidence: 99%